Analysis of Grade VI Students' Mathematical Creative Thinking Skills in Solving Problems on the Topic of Circles - Oktorina Ponco Rahayu; Ristiana Dyah Purwandari (Proceedings Series on Social Sciences & Humanities, 2025)
This research aims to describe how the mathematical creative thinking abilities of grade sixth students in solving mathematical problems on circle material at SD Negeri 1 Mantrianom with the indicators of mathematical creative thinking ability used being fluency, flexibility, originality and elaboration. This research was conducted on 23 class VI students using a qualitative descriptive method. The instrument used was 4 descriptive questions which covered students' mathematical creative thinking abilities on circle material. The results of the research show that students' mathematical creative thinking abilities have a percentage of 62.5% which is included in the category of creative.